Peran Media Penyiaran Dalam Proses Pemulihan Pasca Bencana - Fitri Murfiani (Ornamen, 2006)
Broadcasting media is very important for human life alteration. Radio and television are broadcasting medias which are efisien to reach large audiences. Media has a big attention for disaster, such as earthquake that happened in Yogyakarta. Disaster usually creates uncertain situation. It is also as a big news to be broadcasted by the media. Media must have a control function for the government and social institutions. National television is also limited in spreading/broadcasting informations in a long duration because the television must give an up to date information or we call it a hot news. That is why local media must take more roles in this recovering process.Keyword: Media, Penyiaran, Pasca Bencana.